2020
DOI: 10.1287/isre.2019.0892
|View full text |Cite
|
Sign up to set email alerts
|

Onward and Upward? An Empirical Investigation of Gender and Promotions in Information Technology Services

Abstract: Is there a gender bias in promotions at information technology (IT) companies? Do women get an equal lift in their promotion prospects from performance improvements, work experience, and training as men? These are pertinent and important questions affecting today’s IT human capital. We analyze data from a leading IT services firm using robust econometric techniques to suggest that, contrary to expectations, women are more likely to be promoted. Although we do not find any evidence of overt discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 97 publications
0
9
1
Order By: Relevance
“…An analysis of archival promotion data found that women in IT were more likely to be promoted than men, contrary to the researchers’ predictions (Langer et al., 2020).…”
Section: Bias and Discrimination In The Workplacecontrasting
confidence: 64%
See 1 more Smart Citation
“…An analysis of archival promotion data found that women in IT were more likely to be promoted than men, contrary to the researchers’ predictions (Langer et al., 2020).…”
Section: Bias and Discrimination In The Workplacecontrasting
confidence: 64%
“…In fact, in some fields, men may be held to a higher standard (Madison & Fahlman, 2020). • An analysis of archival promotion data found that women in IT were more likely to be promoted than men, contrary to the researchers' predictions (Langer et al, 2020). • Among German sociologists, women can get tenure with 23-44% fewer publications than men (Lutter & Schr€ oder, 2016).…”
Section: Challenges To the Discrimination Explanation For Stem Gender Gapsmentioning
confidence: 90%
“…First, this study adds to the existing gender disparity in IT literature. Gender disparities are an often-cited concern of the IT workforce (DiSabatino, 2000;Patel and Parmentier, 2005;Trauth et al, 2008;Langer et al, 2020). It has been documented that working women face severe challenges in the IT workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural attitudes about maternity, childcare, parental care, and working outside the home seriously affect a woman's choice of an IT career (Trauth et al, 2008). Women realize less benefit from performance gains than men and less benefit from tenure within IT firms (Langer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The objective is to provide society and the government with information that supports the intragender agenda in urban mobility. Although previous studies have investigated the problems of technology use concerning gender (Primo, 2003;Asiedu, 2012;Foth, 2016;Ibrahim and Adamu, 2016;Karwatzki et al, 2017;Cai et al, 2017;Kottorp et al, 2019;Langer et al, 2020), none of these studies has adopted an intragender perspective regarding the use of urban applications.…”
Section: Introductionmentioning
confidence: 99%